Evaluating effect of alginate/chitosan hydrogel containing 4-Methylcatechol on peripheral nerve regeneration in rat model. Issue 17 (22nd November 2021) - Abbaszadeh-Goudarzi, Ghasem; Haghi-Daredeh, Saeed; Ehterami, Arian; Rahmati, Majid; Nazarnezhad, Simin; Hashemi, Seyedeh Fatemeh; Niyakan, Maryam; Vaez, Ahmad; Salehi, Majid
Abstract: Some of the trauma patients (about 3%) suffer from peripheral nerve injuries and unfortunately, it is still a significant clinical problem to regenerate and functional recovery of them. These days, peripheral nerve damages have been treated with various methods and materials. The goal of the present study is to evaluate the effect of various amounts of 4-Methylcatechol (4-MC) on peripheral nerve regeneration. For this target, alginate/chitosan hydrogel was used to deliver different percentages (0.1%, 1%, and 10% (w/v)) of 4-MC to the sciatic nerve-injured sites in a rat model. Before that, the properties of hydrogels were assessed and after injecting, different functional analyses were used to evaluate the efficacy of fabricated hydrogels on peripheral nerve regeneration. Our results exhibited that the pore size of hydrogels was appropriate for cell proliferation (26–42 µm). Biodegradability of hydrogels was about 70% after 7 days and hemocompatibility of hydrogels was also confirmed. The MTT assay showed that the hydrogels not only do not have toxicity effects but also can improve the proliferation rate of PC12 cells. The functional results showed that 4-MC especially the group contained 10% of 4-MC enhance sciatic nerve regeneration. It could be concluded that fabricated hydrogels can use as suitable materials for peripheral nerve regeneration. Graphical Abstract: UF0001